2005
DOI: 10.1161/01.atv.0000172689.53992.25
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of VLDL 1 Driven by Hyperglycemia Is a Dominant Feature of Diabetic Dyslipidemia

Abstract: Objective-We sought to compare the synthesis and metabolism of VLDL 1 and VLDL 2 in patients with type 2 diabetes mellitus (DM2) and nondiabetic subjects. Methods and Results-We used a novel multicompartmental model to simultaneously determine the kinetics of apolipoprotein (apo) B and triglyceride (TG) in VLDL 1 and VLDL 2 after a bolus injection of [ 2 H 3 ]leucine and [ 2 H 5 ]glycerol and to follow the catabolism and transfer of the lipoprotein particles. Our results show that the overproduction of VLDL pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
181
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(198 citation statements)
references
References 37 publications
16
181
0
1
Order By: Relevance
“…There was a strong linear correlation between the ApoB and TG pools in all subjects (r=0.98, p<0.001). This finding is consistent with our earlier results [3] …”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…There was a strong linear correlation between the ApoB and TG pools in all subjects (r=0.98, p<0.001). This finding is consistent with our earlier results [3] …”
Section: Discussionsupporting
confidence: 94%
“…Type 2 diabetic subjects produced significantly (p<0.01) more VLDL 1 TG and ApoB than non-diabetic subjects (Table 2), confirming our previous findings [3]. There was also a significant increase (p=0.04) in direct production of VLDL 2 , TG but no significant difference in direct production of VLDL 2 ApoB.…”
Section: Production and Clearance Ratessupporting
confidence: 88%
See 2 more Smart Citations
“…The results of this study suggest that the hypoglycemic effect of pioglitazone is achieved mainly through improvement of hepatic insulin resistance, and that pioglitazone have an antiatherosclerotic effect by decreasing serum atherogenic modified-LDL and increasing adiponectin. [22][23][24]. Griffin and Packard [25,26] demonstrated that large VLDL1 is a precursor of small dense LDL, and that it is produced preferentially in the liver during development of insulin resistance.…”
Section: Changes Of Lipoprotein Subclasses According To Particle Sizementioning
confidence: 99%